“Not really much of a choice”: Frontline violence against women shelter workers’ perspectives on police intervention in intimate partner violence - Huang, Xin (Mona) (My University, 2025)
As one of the key institutions responding to intimate partner violence (IPV), the police are often the first point of contact for women experiencing violence. While police involvement is intended to provide immediate relief and protection for survivors of violence, it can also produce unintended negative outcomes, particularly for systemically marginalized groups (Aujla, 2021; Duhaney, 2022; Garza et al., 2022; Wachholz & Miedema, 2000). Informed by anti-carceral feminism and transformative justice, this thesis sought to explore the effects of police intervention in IPV and its implications for social work practice through the perspectives of frontline violence against women (VAW) shelter workers. Four frontline VAW shelter workers from the Greater Toronto Area participated in the research to share their experiences working with the police. The findings illuminated (1) workers’ perspectives on IPV, and responses needed to address this issue, (2) the complexities of police intervention in IPV where workers shared what they felt was working and what was not, (3) the constraints on women’s choice and safety as a result of police intervention, and (4) workers’ call for more options to address IPV outside the criminal legal framework. As an exploratory study, this project contributes to a better understanding of the impact of a carceral response to IPV on both women who experience violence and frontline shelter workers who engage with the police in their practice. It also holds implications for anti-violence efforts in research, policy, and social work practice.
Keywords: intimate partner violence; criminalization; anti-carceral feminism; transformative justice; narrative inquiry